PENGARUH GROSS PROFIT MARGIN (GPM) DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP PERTUMBUHAN LABA (NET PROFIT GROWTH) PADA PT MATAHARI DEPARTMENT STORE TBK PERIODE 2014-2024 - Aprilianti, Fernanda Cahya; Nurwita, Nurwita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to analyze the effect of Gross Profit Margin (GPM) and Operating Expenses to Operating Income (BOPO) on Profit Growth at PT Matahari Department Store Tbk for the 2014-2024 period using a quantitative associative method. Data were analyzed using multiple linear regression and hypothesis testing via SPSS version 26 software. The results indicate that, both partially and simultaneously, GPM and BOPO do not have a significant effect on the company's profit growth. This proves that a stable gross profit margin does not necessarily guarantee an increase in net profit, primarily due to high fluctuations in operating expenses and the dominant influence of external factors outside the research model on the company's profit changes.